Bilateral Cooperation between Indonesia and Malaysia in Combating Transnational Crime - Mustofa, Muhammad (Indonesian Journal of International Law, 2008)
This paper us discuss that bilateral cooperation between Indonesia and Malaysia in combating transnational crime or trans-border crime. First of all, it should be based on understanding the root of the problem in trans-border crime problems. Furthermore, the effective bilateral cooperation can occur when notice the same aspects in the definition of the crime, the existence of law, the recognition of the evidence, extradition agreement, and the network information between the states.